Integrating DSM-IV factors to predict violence in high-risk psychiatric patients - Lynch, Donna M.; Noel, Helen C. (Journal of Forensic Sciences, 2010)
This study incorporated Axis-II and Axis-IV factors in DSM-IV to test the relationship between predicted risk for violence assessed in the psychiatric emergency room and actual violence during hospitalization. Psychiatric nurses lack an objective instrument to use during the acute psychiatric assessment. The retrospective study comprised consecutive psychiatric admissions (n = 161) in one tertiary veterans' hospital. Statistical testing for the predictive power of risk factors, relationships between variables, and violent events included nonparametric tests, factor analysis, and logistic regression. Of the 32 patients who committed violence during hospitalization, 12 had committed violence in the psychiatric emergency room. Statistical significance was shown for violent incidents and dementia, court-ordered admission, mood disorder, and for three or more risk factors. The 13-item Risk of Violence Assessment (ROVA) scale suggests validity and sensitivity for rating DSM-IV factors and psychosocial stressors to predict risk for violence during hospitalization. Replication studies are recommended to strengthen validity of the ROVA scale.
Keywords: Adult; Aged; Aged, 80 and over; Aggression; Assault; Assessment; Commitment of Mentally Ill; Dementia; Diagnostic and Statistical Manual of Mental Disorders; Diagnostic and statistical manual of mental disorders (DSM-IV); Emergency Services, Psychiatric; Female; Forensic Psychiatry; Forensic science; Hospitals, Veterans; Humans; Instrument; Male; Mental Disorders; Middle Aged; New England; Psychiatric; Psychiatric Status Rating Scales; Reproducibility of Results; Retrospective Studies; Risk Assessment; Risk factors; Self-harm; Suicidal; United States; Violence; adult; aged; article; dementia; dept.psy; diagnostic and statistical manual of mental disorders; emergency health service; female; forensic psychiatry; human; male; mental disease; middle aged; psychological aspect; psychological rating scale; public hospital; reproducibility; retrospective study; risk assessment; violence

Distinguishing truthful from invented accounts using reality monitoring criteria - Memon, Amina; Fraser, Joanne; Colwell, Kevin; Odinot, Geralda; Mastroberardino, Serena (Legal and Criminological Psychology, 2010)
Purpose. Previous research has suggested that true and invented memories can be distinguished between using the reality monitoring criteria. Two different coding schemes were used to examine the correct classification of reports as truthful or deceptive on the basis of individual reality-monitoring (RM) criteria. Method. Drawing upon the RM framework the present experiment examined transcripts of verbal accounts of eyewitnesses to a staged event or made up details about the incident. The statements were elicited during a face-to-face cognitive interview (CI) and were analysed by coders trained in the identification of criteria indicative of self-experienced and invented accounts (referred to here as Version 1) and a similar coding method (referred to here as Version 2). Results. A distinction was made between `external memories' (affective, perceptual, and contextual details) and `internal' memories (cognitive operations). For Version 1, the results indicated a higher number of contextual and external details in the descriptions of experienced events and as is commonly found in the deception literature, truthful accounts were longer. For Version 2, temporal and auditory details were more frequent in true accounts. Contrary to prediction, there were also more references to cognitive operations in true accounts. Conclusions. Any forensic application of RM should consider how external factors (characteristics of the event, motivation to deceive, and questioning style) influence the presence of RM criteria.
Keywords: adult; article; coding; cognition; controlled study; dept.psy; female; human; interview; major clinical study; male; memory; monitoring; priority journal; questionnaire; reality monitoring; self concept; verbal communication; witness

Distributed versus exclusive preference in discrete-trial choice. - Mazur, James E (Journal of Experimental Psychology: Animal Behavior Processes, 2010)
Two experiments on discrete-trial choice examined the conditions under which pigeons would exhibit exclusive preference for the better of two alternatives as opposed to distributed preference (making some choices for each alternative). In Experiment 1, pigeons chose between red and green response keys that delivered food after delays of different durations, and in Experiment 2 they chose between red and green keys that delivered food with different probabilities. Some conditions of Experiment 1 had fixed delays to food and other conditions had variable delays. In both experiments, exclusive or nearly exclusive preference for the better alternative was found in some conditions, but distributed preference was found in other conditions, especially in Experiment 2 when key location varied randomly over trials. The results were used to evaluate several different theories about discrete-trial choice. The results suggest that exclusive preference for one alternative is a frequent outcome in discrete-trial choice. When distributed preference does occur, it is not the result of inherent tendencies to sample alternatives or to match response percentages to the values of the alternatives. Rather, distributed preference may occur when two factors (such as reinforcer delay and position bias) compete for the control of choice, or when the consequences for the two alternatives are similar and difficult to discriminate.
Keywords: *Choice Behavior/ph [Physiology]; *Conditioning, Operant/ph [Physiology]; *Reinforcement Schedule; *Reinforcement, Psychology; Animals; Choice Behavior; Columba; Columbidae; Conditioning, Operant; Discrete-trial choice; Exclusive preference; Male; Pigeons; Probability; Reaction Time; Reaction Time/ph [Physiology]; Reinforcement (Psychology); Reinforcement Schedule; Reinforcer delay; Time Factors; animal; article; decision making; dept.psy; instrumental conditioning; male; physiology; pigeons and doves; probability; reaction time; reinforcement; time

Impression management strategies of deceivers and honest reporters in an investigative interview - Hines, Amber; Colwell, Kevin; Hiscock-Anisman, Cheryl; Garrett, Erika; Ansarra, Ryan; Montalvo, Larissa (European Journal of Psychology Applied to Legal Context, 2010)
Understanding the subjective experience of respondents attempting to convince an investigator will enhance our theoretical knowledge of deception and improve assessment techniques. Discrepancies between respondents' understanding and actual credibility criteria are especially important. Sixty-six participants engaged in a small crime, and were interviewed following a week's preparation. All were provided incentive for convincing the interviewer of the veracity of their statement. Thirty-two were honestly reporting the theft, and thirty-four were responding to avoid being found guilty. After a Reality Interview (a derivative of the Cognitive Interview), participants were asked to describe what was important in convincing the interviewer through open-ended and Liken-type questions. These strategies of impression management are presented here. The basic task of convincing appeared similar for both groups, with participants focused on providing clear and careful stories without contradictions rather than attempting to provide vivid and spontaneously-constructed statements. Deceivers attached more importance to: I) preparing in advance, 2) monitoring and controlling information, and 3) maintaining eye contact. Honest respondents were more concerned with providing correct peripheral detail. Importantly, both groups were reporting much more similarity than difference, and the strategies described are not likely to succeed against verbal content analysis.
Keywords: Credibility; Deception; Interrogation; Testimony; Verbal communication; dept.psy; ⛔ No DOI found